(untitled) (LEARNing Landscapes, 2010)
Bilingualism in French and English is a much-to-be hoped for common and shared characteristic of Canadian citizenship—even though to date the effect of forty years of the Official Languages Act has been most marked in government services and among various Canadian elites. Although it is important that Canada hold onto a goal of the widest possible bilingualism, more modest objectives are outlined for the years immediately ahead.